Brief report on combat trauma surgical training using a perfused cadaver model. Issue 2 (August 2020) - Grabo, Daniel; Polk, Travis; Minneti, Michael; Inaba, Kenji; Demetriades, Demetrios
Abstract : BACKGROUND: Surgical combat casualty care presents difficult training challenges. Although several high-fidelity simulation (SIM) techniques have emerged, none are able to fully integrate the many intricacies involved in the care of a complex trauma patient. Herein, we report the use of perfused fresh human cadaver model for training and assessment of forward surgical teams (FSTs). METHODS: Forward surgical teams attend a 4-day combat trauma surgical skills course including focused on trauma exposures. A half-day SIM involves the entire surgical team in four sequential surgical scenarios that involve the neck, chest, abdomen, and extremities, as well as airway management and resuscitation. Teams undergo immediate debriefing and videotape review of team dynamics and technical skills, as well as times to completion of critical interventions. RESULTS: The data evaluated include five initial demonstration courses in which training metrics were available. Each team included both a junior and experienced surgeon, anesthesiologists, and surgical scrub technicians. As FSTs progressed through SIMs, they demonstrated improvements in team dynamics and technical skills evaluations. There was considerable variability in the times to completion of critical intervention, particularly for control of cardiac and vascular injuries. CONCLUSION: Initial evaluations support the use of this novel perfused cadaver model for the training and evaluation of military FSTs. Preliminary data highlight the utility for open vascular, thoracic, and other high-acuity/low-volume procedures critical to combat casualty care. Larger studies are needed for model optimization and further validation of an objective structured technical assessment tool. LEVEL OF EVIDENCE: Care management, level V.